Efficiency Analysis of Honey Encryption Algorithm - Bhoomika, R; Narsimha, Gowda Deepa; Abhishek, V; Bharathi, H (International Journal of Computer Sciences and Engineering, 2025)
In the field of cyber security, we have many algorithms that support cryptography. These algorithms are more prone to cyber-attacks and can be cracked easily by hash cracking tools. One of the methods to prevents these attacks is Honey Encryption technique that has gained popularity in recent years. This method provides another layer of protection when the intruder tries to hack an account with bogus data. In this paper, we are efficiently increasing the probability of Honey Encryption by generating more hash keys(password)using python programming approach. Honey encryption helps in minimization of vulnerability. We have designed an algorithm which eventually increases the buffer size for the randomly generated passwords.